Cost-effectiveness of Catheter Ablation Versus Antiarrhythmic Drug Therapy for the Treatment of Atrial Fibrillation: A Canadian Perspective - Yaariv Khaykin; Peter J. Mallow; John A. Rizzo; Atul Verma; Lauren Chun; Shelby Olesovsky; Matthew R. Reynolds (Journal of Health Economics and Outcomes Research)
**Background:** Atrial fibrillation (AF) affects approximately 350,000 Canadians and has an estimated annual economic burden exceeding $800 million dollars. Anti-arrhythmic drug (AAD) therapy and catheter ablation (CA) are the two common treatments for paroxysmal AF. However, the upfront costs of CA are quite substantial.